BALANCED SCORECARD SEBAGAI PENGUKURAN KINERJA PADA PT MITRAKARYA JAYA MANDIRI - Evi Yulianti; Lucia Ari Diyani (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2017)
The purpose of this study is to determine the performance of the company through four main perspectives of financial perspective, customer, internal business and learning and growth. Data analysis techniques using descriptive quantitative and qualitative. The variables used in the financial perspective are Return On Equity, Return On Assets, Profit Margin On Sales, Sales Growth Rate, on customer perspective using Customer Satisfaction Index variable, Customer Retention Rate, Customer Acquisition and Number of Complaints, on internal business perspective using percentage variables Broken product and percentage of products delivered on time, on learning and growth perspective using Employee Satisfaction Index variable, Employee Retention and Employee Training. The result of the research shows that the performance of PT Mitrakarya Jaya Mandiri in financial perspective is considered not very good, the customer perspective is considered good, internal business perspective is considered less good and the learning and growth perspective is considered good. Overall company performance in 2012-2015 is classified under "Less Healthy", BBB category with Total Score Performance = 53,40%. Keywords: Balanced Scorecard, Financial Perspective, Customer Perspective, Internal Business Perspectives, Learning and Growth Perspective